If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) = 3(x + -7) Reorder the terms: 5(1 + x) = 3(x + -7) (1 * 5 + x * 5) = 3(x + -7) (5 + 5x) = 3(x + -7) Reorder the terms: 5 + 5x = 3(-7 + x) 5 + 5x = (-7 * 3 + x * 3) 5 + 5x = (-21 + 3x) Solving 5 + 5x = -21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 5x + -3x = -21 + 3x + -3x Combine like terms: 5x + -3x = 2x 5 + 2x = -21 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 2x = -21 + 0 5 + 2x = -21 Add '-5' to each side of the equation. 5 + -5 + 2x = -21 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = -21 + -5 2x = -21 + -5 Combine like terms: -21 + -5 = -26 2x = -26 Divide each side by '2'. x = -13 Simplifying x = -13
| y-28=50 | | 0.8+d=-0.7 | | 1*(1+x^3)=1.5 | | x^2m-x^2-2x+2m-3=0 | | 3x-20+90+x=180 | | x^2+3x-6=-6 | | 16=2(3c-9) | | 2y+3=8.6 | | 15+a=-10 | | 8-2x=9x+2 | | -16=x+16 | | -5(-6w+5)-9w=7(w-4)-9 | | 0,5-3x=x+1.1 | | 16a-6.5=9.5 | | 2x+3x-15=12+8 | | 3b^2-60b+36=0 | | -7-8(1+6f)=27 | | 5x^2-20x+27=5 | | 4m+-10= | | X+7+x-8+90=180 | | -43=m+21 | | (b-9)(b-4)=0 | | 2b+1=-4+3b | | -2.1+u=3.5 | | 3s^3+12s+8=0 | | 27+yi=24-x+8i | | -3+4=5x-2 | | x^2-8x+73=-4 | | 7/x=1/.5 | | 92-41= | | -9=d-1 | | 2b^2-20b+36=o |